Human Resources Strategies: From Job Satisfaction to Innovation in the Age of Technostress - Bai, Ali; Hessari, Hassan; Daneshmandi, Fatemeh; Nategh, Tahmineh (PT. Riset Press International, 2024)
Employee innovation is a crucial aspect of organizations in the current era. Therefore, studying the factors influencing individual innovation is vital and unavoidable. Undoubtedly, job satisfaction is a significant variable in management sciences. Nowadays, all organizations are interconnected with technology. This research explores the relationship between job satisfaction and individual innovation, including its components and the moderating role of technostress. This study, in terms of purpose, is applied, and in terms of data collection method, it is a descriptive survey. Data collection tools included the Technostress Inventory by Tarafdar and colleagues (2007), Janssen's Individual Innovation Questionnaire (2000), and the Job Satisfaction Survey (JSS) by Spector (1994). The validity and reliability of these questionnaires were confirmed. The sample size for this study was 215, and data analysis was performed using SPSS and SMART-PLS software. Job satisfaction has a significant and positive relationship with individual innovation, idea generation, idea promotion, and idea implementation. Technostress moderates the relationship between job satisfaction and individual innovation, idea generation, and idea promotion. However, technostress does not play a moderating role in the relationship between job satisfaction and idea implementation. Conclusion: Based on the results, organizations should take necessary measures to increase job satisfaction and reduce employee technostress.